Landslide Disaster Preparedness For Residents in Nyarumkop Village Singkawang Timur - Evinna Cinda Hendriana; Buyung Buyung; Slamat Fitriyadi; Mariyam Mariyam; Nindy Citroresmi Prihatiningtyas (STKIP Singkawang, 2018)
ABSTRACTThe purpose ofthis activity is to educate the community to know the symptoms of landslides and increase community awareness early on and provide assistance to the community to identify layers of soil or rocks that have the potential to cause landslides around residential areas using geoelectric. To achieve this goal, landslide disaster preparedness counseling activities are carried out for residents of Nyarumkop Singkawang Timur Village. The number of participants of the activity as many as 20 heads of families. Counseling activities carried out include coordination with the East Singkawang Sub-District and local RT, material briefings, simulation of landslide disaster mitigation, identification of potential landslides, and follow-up activities. The results of this community pengabdian activities can be described as follows: The community has been aware of the symptoms of landslides and there is an increase in public awareness early on. The community has also known the layers of soil or rocks that have the potential to cause landslides around their residential areas, namely limestone layers with layers of the top of the field of derailment in the form of clay, clay sand, and sandstone that can store water contentABSTRACTThe purpose ofthis activity is to educate the community to know the symptoms of landslides and increase community awareness early on and provide assistance to the community to identify layers of soil or rocks that have the potential to cause landslides around residential areas using geoelectric. To achieve this goal, landslide disaster preparedness counseling activities are carried out for residents of Nyarumkop Singkawang Timur Village. The number of participants of the activity as many as 20 heads of families. Counseling activities carried out include coordination with the East Singkawang Sub-District and local RT, material briefings, simulation of landslide disaster mitigation, identification of potential landslides, and follow-up activities. The results of this community pengabdian activities can be described as follows: The community has been aware of the symptoms of landslides and there is an increase in public awareness early on. The community has also known the layers of soil or rocks that have the potential to cause landslides around their residential areas, namely limestone layers with layers of the top of the field of derailment in the form of clay, clay sand, and sandstone that can store water content.